2018
DOI: 10.1007/978-3-030-00066-0_45
|View full text |Cite
|
Sign up to set email alerts
|

Anonymized Distributed PHR Using Blockchain for Openness and Non-repudiation Guarantee

Abstract: We introduce our solution developed for data privacy, and specifically for cognitive security that can be enforced and guaranteed using blockchain technology in SAAL (Smart Ambient Assisted Living) environments. Using our proposal the access to a patient's clinical process resists tampering and ransomware attacks that have recently plagued the HIS (Hospital Information Systems) in various countries. One important side effect of this data infrastructure is that it can be accessed in open form, for research purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…For example, non-repudiation assures others about the creator and origin of data when each user is responsible for creating their data. Besides this, non-repudiation also confirms the data integrity of the users in the network [212].…”
Section: Security Propertiessupporting
confidence: 55%
“…For example, non-repudiation assures others about the creator and origin of data when each user is responsible for creating their data. Besides this, non-repudiation also confirms the data integrity of the users in the network [212].…”
Section: Security Propertiessupporting
confidence: 55%
“…Li et al [ 20 ] presented a medical data preservation system based on the real-world blockchain platform Ethereum, which provides a trustworthy storage solution to ensure the primitiveness and verifiability of stored data. Mendes et al [ 22 ] presented a Smart Ambient Assisted Living environment, which uses blockchain technology to enhance data privacy and cognitive security in the health care sector. As noted above, out of the 22 included papers, 3 (14%) were high-quality papers, 9 (41%) were moderate-quality papers, and 10 (45%) were low-quality papers.…”
Section: Discussionmentioning
confidence: 99%
“…Kleinaki et al [ 28 ] implemented a blockchain-based notarization service that uses smart digital contracts to secure data in the biomedical research sector. A study by Mendes et al [ 22 ] showed that after the retrieval process, retrieved data cannot be modified, which ensures the integrity and nonrepudiation of the data. Using blockchain technology, data versioning was achieved where medical evidence of different versions of data retrieved from a biomedical database were securely stored and saved, along with content that is continually updated.…”
Section: Discussionmentioning
confidence: 99%
“…Blockchain technology has great potential for electronic health records [ 13 ]. The core of the blockchain model ensures that any information involved has nonrepudiation to maintain the correctness of the historical process records [ 14 ]. Gary et al [ 15 ] Reviewed the current PHR definitions and multiple blockchain architectures for PHR management and found that blockchain technology is a key requirement for the management of consent to use private health data.…”
Section: Discussionmentioning
confidence: 99%